Tryptophan, uric acid, and dopamine detected simultaneously using an accurate and affordable electrochemical sensor based on Co9S8-supported electrochemically reduced graphene oxide - Peihong Deng; Aiting Chen; Shuting Shi; Chuanqin Zhou; Nana Tang; Quanguo He (Results in Engineering)
A cost-effective and simple electrochemical approach was developed for the simultaneous detection of tryptophan (Trp), uric acid (UA) and dopamine (DA). Through hydrothermal synthesis, Co9S8 was combined with graphene oxide (GO) using physical ultrasound. Subsequently, the Co9S8-RGO/GCE was created by electrochemically reducing a Co9S8-GO dispersion after drop-coating it onto the GCE surface. The amalgamation of Co9S8 with RGO conferred the sensor with remarkable sensitivity, outstanding selectivity, and robust catalytic prowess towards DA, UA and Trp. The ternary mixture exhibited notable peak separations of up to 160 mV, 278 mV, and 438 mV between DA–UA, UA–Trp, and DA–Trp, respectively. The linear calibration ranges spanned 0.1–2.0 μM and 2.0–10 μM for DA, 0.06–10 μM for UA, and 0.02–10 μM for Trp, with matching 0.04 µM for DA, 0.02 µM for UA, and 6.0 nM for Trp detection limits (S/N = 3). Moreover, the sensor's effective use in the identification of DA, UA and Trp in authentic samples yielded satisfactory results.